Pipeline scour rates prediction-based model utilizing a multilayer perceptron-colliding body algorithm - Ehteram M.; Ahmed A.N.; Ling L.; Fai C.M.; Latif S.D.; Afan H.A.; Banadkooki F.B.; El-Shafie A. (MDPI AG, 2023)
Forecasting; Multilayers; Particle swarm optimization (PSO); Pipelines; Soft computing; Colliding bodies; MLP model; Multi layer perceptron; Optimization algorithms; Optimization modeling; Prediction model; Soft computing models; Wave characteristics; Scour; algorithm; hydrological modeling; model; optimization; pipeline; scour; Cetacea